The transition from public to private in probation: Values and attitudes of managers in the private sector. (September 2014) - Deering, John; Feilzer, Martina; Holmes, Tim
This article reports the values and attitudes of a small sample of managers working for the private sector in criminal justice roles. All had previously had careers within the probation service. Their reasons for moving are discussed, along with their views of the relative merits of public and private criminal justice provision. In the main, their views appear underpinned by a clear acceptance of the legitimacy of a role for the private (and third sectors) in the criminal justice system that echo recent pronouncements by the Coalition government. However, their values in other regards reflect what might be seen to be more 'traditional probation values'.